2015
DOI: 10.3923/ajpnft.2015.71.78
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chicken Manure Integration with Mineral Fertilizer on Soil Nutriments Balance and Maize (Zea mays) Yield: A Case Study on Degraded Soil of Lubumbashi (DR Congo)

Abstract: One of the most important challenges to continuously maximize crop production on limited areas of agricultural land is to maintain or enhance soil fertility. Organic fertilizer application is needed to replace nutrient removed by crop from the fields in order to restore crop production potential of a soil. But application of organic fertilizer alone insufficiently increases crop yield per area because the nutrient content of organic fertilizer is unbalanced. A trial was conducted in the Lubumbashi region to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 4 publications
2
9
0
2
Order By: Relevance
“…This finding is in agreement with other studies, where they showed fertilization with PM gave higher crop yield compared with CM (Detpiratmongkol et al, 2014;Ghosh et al, 2004;Kidinda et al, 2015). The better performance of PM in supporting wheat crop maybe is related to its low C/N ratio (i.e.…”
Section: Root Straw Ears and Total Biomasssupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is in agreement with other studies, where they showed fertilization with PM gave higher crop yield compared with CM (Detpiratmongkol et al, 2014;Ghosh et al, 2004;Kidinda et al, 2015). The better performance of PM in supporting wheat crop maybe is related to its low C/N ratio (i.e.…”
Section: Root Straw Ears and Total Biomasssupporting
confidence: 92%
“…In this study, application of NDM and DM increased plant height significantly compared with urea treatment, which is in agreement with the other studies where organic fertilizer showed better plant growth and yield compared to mineral fertilizer (Abubaker et al, 2012;Kidinda et al, 2015). Furthermore, the results clearly reveal that plant height was affected significantly by nitrogen source, as shown from the height recorded in the treatment of DCM where it produced taller plant than non-digested.…”
Section: Seed Germination Plant Tillering and Plant Heightsupporting
confidence: 91%
See 1 more Smart Citation
“…This feedstock vary substantially in chemical composition, particle size and also its decompositions rates . Among this, chicken manure also has been found to be rich in nutrients such as nitrogen (N), phosphorus (P), calcium (Ca), potassium (K) and magnesium (Mg) [4]. Poultry manure had significantly improve the soil physical properties, enhanced the nutrient uptake and the growth and yield [5].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative way to improve the physical and biological properties of soil and consequently to increase crop yields is to use organic fertilizers (alone or in combination with mineral fertilizers), such as animal litter, green manure or compost (Melkamu, 2012). The efficacy of organic fertilizers for improving maize growth, grain and dry matter yields, and/or harvest index has previously been demonstrated (Ademba et al, 2014(Ademba et al, , 2015Kidinda et al, 2015;Martins et al, 2017;Baghdadi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%